ECOLOGICAL AND ECONOMIC ASSESSMENT OF THE POTENTIAL OF AGRICULTURAL LAND - Orest FURDYCHKO; Roman HULINCHUK; Iryna SAMOILOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Improved methodological approach to the environmental and economic assessment of the potential of agricultural land which is based on the use of an integral index, which sufficiently characterizes the properties, functions and possibilities of using land resources in agricultural production. The integral index of the potential of agricultural land was proposed to be calculated as the average value of the normalized indicators of agroclimatic potential, soil bonitet and regulatory and monetary assessment of land. This approach allows us to determine in the future the objective level and efficiency of using the potential of agricultural land both at the level of territories and economic entities. An environmental-economic assessment of the potential of agricultural land in the Kiev region. On the basis of theoretical and methodological approaches, an assessment was made of the effectiveness of the use of the potential of agricultural land in the districts of the Kiev region. The proposed approach provided for comparing the cost estimates of the theoretical and actual productivity of land resources in agriculture, calculated on an integral score of the potential of agricultural land. The evaluation results indicate that the level of use of the potential of agricultural land varies from 31.8 to 293.8 %. It was found that eight districts of the region use the potential of agricultural land at a low level, and in most areas the actual figures exceed the theoretical one by 1-2 times.